2019
DOI: 10.1177/0306312719864164
|View full text |Cite
|
Sign up to set email alerts
|

Filling in the gaps: The interpretation of curricula vitae in peer review

Abstract: In this article, we study the use of curricula vitae (CV) for competitive funding decisions in science. The typically sober administrative style of academic résumés evokes the impression of straightforwardly conveyed, objective evidence on which to base comparisons of past achievements and future potentials. We instead conceptualize the evaluation of biographical evidence as a generative interplay between an historically grown, administrative infrastructure (the CV), and a situated evaluative practice in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…According to our synthesis, which is mostly based on studies on project funding, peers evaluate the applicant in terms of a resource needed to implement the proposed project (instrumental role). In fellowship programs, however, peers evaluate the applicant also in order to decide whether she/he is suited for a further step in her/his academic career (Kaltenbrunner and de Rijcke, 2019). Lastly, our findings depend on the choices made in the included studies, such as the number of reported criteria, the level of abstraction of the reported criteria, or the words used to describe the criteria.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…According to our synthesis, which is mostly based on studies on project funding, peers evaluate the applicant in terms of a resource needed to implement the proposed project (instrumental role). In fellowship programs, however, peers evaluate the applicant also in order to decide whether she/he is suited for a further step in her/his academic career (Kaltenbrunner and de Rijcke, 2019). Lastly, our findings depend on the choices made in the included studies, such as the number of reported criteria, the level of abstraction of the reported criteria, or the words used to describe the criteria.…”
Section: Discussionmentioning
confidence: 91%
“…Rather, we understand it as a repertoire from which peers choose when PALGRAVE COMMUNICATIONS | https://doi.org/10.1057/s41599-020-0412-9 REVIEW ARTICLE PALGRAVE COMMUNICATIONS | (2020) 6:37 | https://doi.org/10.1057/s41599-020-0412-9 | www.nature.com/palcomms assessing grant applications. In addition, we conceive the evaluation criteria (and evaluated entities) as situated concepts (Yeh and Barsalou, 2006) that are (re)shaped by the actual assessment in which they are enacted (Kaltenbrunner and de Rijcke, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to our synthesis, which is mostly based on studies on project funding, peers evaluate the applicant in terms of a resource needed to implement the proposed project (instrumental role). In fellowship programs, however, peers evaluate the applicant also in order to decide whether she/he is suited for a further step in her/his academic career (Kaltenbrunner & de Rijcke 2019). Lastly, our findings depend on the choices the included studies have made, such as the number of reported criteria, the level of abstraction of the reported criteria, or the words used to describe the criteria.…”
Section: Discussionmentioning
confidence: 90%
“…While this provides him with a robust typology of appraisal devices, it does not let him pay sufficient attention to what I call practices of appraisal devices – that is, the processes by which actors engage with and interpret appraisal devices, including how they decide the criteria and means for using or disputing them in concrete situations. Indeed, the devices theory has recently been criticized for its reductive and functionalistic tendencies when applied in studies of academic evaluation (Kaltenbrunner and de Rijcke 2019 ). However, focusing on practices of appraisal devices, this paper tackles such criticism by emphasizing the reflexive work required by actors using them.…”
Section: Theorizing Practices Of Appraisal Devicesmentioning
confidence: 99%